Mengukur Tingkat Kemampuan Koneksi Matematis Siswa SMP Kelas VIII pada Materi Garis Singgung Lingkaran - Nurhasanah, Nurhasanah; Hanifah, Hanifah; Kartika, Hendra (EDUPEDIA PUBLISHER, 2022)
The purpose of this study was to measure the level of mathematical connection ability of class VIII junior high school students on the material of tangents to circles. The approach of this research is quantitative with case study design. The sample of this study was 50 students of class VIII who were selected by quota sampling in one of the public junior high schools in Karawang, West Java. The analysis used is descriptive statistical data analysis by measuring the level of ability possessed by class VIII students at the school. The results showed that from 50 students there were 32% students who were still classified as low mathematical connection abilities. The results of this study indicate that it is necessary to strengthen learning, one of which is peer teaching of students with high mathematical connection abilities or teacher scaffolding.